1990
DOI: 10.1351/pac199062112097
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics and structure in nonelectrolyte solutions

Abstract: Thermodynamic quantities, particularly second-order are indicators of structure both in the pure components and in solution. Three solution structures are treated: (1) Non-randomness or concentration fluctuations due to "antipathy" between the components. This gives rise to a W-shape concentration dependence of the excess heat capacity CpE. Systems containing polyethers and alkanes illustrate the effect of molecular size on the W-shape CpE and its relation with a quantitative measure of nonrandomness calculate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 3 publications
2
20
0
Order By: Relevance
“…The results showing that the "W-shape" is enhanced as the temperature approaches the critical solubility temperature were previously published (e.g. [2][3][4][5]8]). This phenomenon has been explained qualitatively by an enhancement of non-randomness and local fluctuations in a liquid solution that is close to the critical solubility point.…”
Section: Introductionsupporting
confidence: 60%
See 3 more Smart Citations
“…The results showing that the "W-shape" is enhanced as the temperature approaches the critical solubility temperature were previously published (e.g. [2][3][4][5]8]). This phenomenon has been explained qualitatively by an enhancement of non-randomness and local fluctuations in a liquid solution that is close to the critical solubility point.…”
Section: Introductionsupporting
confidence: 60%
“…After the regression, the composition of the coexisting phases was calculated from the parameters of Eq. (8). This reverse calculation showed that the maximum deviation between the calculated and experimental composition was 0.008 in the mole fraction, and the average deviation was about 0.003.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…That expression is symmetric with respect to each component of the mixture and ε e (v i = 1) = ε i . Table 1 shows the comparison of measured equivalent permittivity and values calculated using equation (20) for a liquid mixtures of an apolar solvent, n-nonane, with a polar solute, tetra(ethylene glycol) dimethyl ether (also named tetraglyme) for a complete range of composition and at T = 298.15 K. This mixture presents a consolute point close to T = 288 K. Then one can reasonably expect that above this temperature, the mixture presents local aggregates of its pure components as Andreoli-Ball (10) has suggested from thermodynamic arguments. Experimental results were obtained in our laboratory.…”
Section: A New Expression For the Effective Permittivity Of Mixturesmentioning
confidence: 99%